The Social Safety Nets and Poverty Alleviation in Pakistan: An Evaluation of Livelihood Enhancement and Protection Programme - Asif Javed; Vaqar Ahmed; Bakhrul Khair Amal (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
Sustainable Development Goal (SDG) 1 intends to end poverty of all forms and the government of Pakistan is also targeting poverty alleviation through social safety nets. ‘Ehsaas’ is the major social safety nets proramme which include various initiatives that are benefiting millions of households. The study examines the state of poverty in Pakistan and also highlights the spending under each social safety net. Furthermore, the study also evaluates the Livelihood Enhancement and Protection (LEP) programme which is a major initiative for poverty alleviation under Ehsaas programme. Survey in Khyber Pakhtunkhawa and Balochistan provinces were conducted of those beneficiaries who are getting asset and skills training. It was found that asset provision and skills trainings are helpful in increasing the earnings and provide sustainable livelihood opportunities to poor households.